Предмет: Алгебра,
автор: Аноним
Даю 100 балов за 100% правильный ответ
Приложения:
![](https://files.topotvet.com/i/354/354e54d596a485c6f48dacf77c027e6a.png)
Wiskaskiskas149:
Чочрчис
Ответы
Автор ответа:
0
Объяснение:
|5х - 4(2х + 3)| = 6
1)
5х - 4(2х + 3) = -6
5х - 8х - 12 = -6
-3х - 12 = -6
-3х = -6 + 12
-3х = 6
х = 6 : (-3)
х1 = -3
2)
5х - 4(2х + 3) = 6
5х - 8х - 12 = 6
-3х - 12 = 6
-3х = 6 + 12
-3х = 18
х = 18 : (-3)
х2 = -6
Ответ: -3; -6
(х + 8)/3 - (х - 2)/5 = 2 | * 15
5(х + 8) - 3(х - 2) = 30
5х + 40 - 3х + 6 = 30
2х + 46 = 30
2х = 30 - 46
2х = -16
х = -16 : 2
х = -8
Похожие вопросы
Предмет: Математика,
автор: akairolda
Предмет: Українська мова,
автор: mikhail2011ole
Предмет: Геометрия,
автор: Аноним
Предмет: Математика,
автор: dashaoiila
Предмет: Алгебра,
автор: igifufirissiz346